5. منافع الأفعال الثلاثي المزيد في كتاب بلوغ المرام "الباب الطهارة - Mohammad Zainal Hamdy; Holis Abdullah (Riyahuna: Jurnal Pendidikan Bahasa Arab, 2022)
The science of Arabic is the science which attains the perfection of the tongue and pen from error, and they are thirteen sciences: morphology, grammar, drawing, meaning, statement, beautiful, prosody, verse, borrowing poetry, composition, rhetoric, literary history, and body. language. The study of morphology looks for words before they are arranged in sentences from their original form to the changes that occur in them. The research that the researcher will try to do in this research is as follows: What are the three verbs added in the book Bulugh al-Maram (chapter of chastity)? What are the benefits of three more verbs in the book Bulugh al-Maram (Chapters of Chastity)? This research is included in several types of library research. What is meant by library research is research conducted by researchers inside or outside the library for all facts or data from types of books. The addition of three verbs mentioned in the Kitab Bulugh al-Maram (Chapters of Chastity) is reported in a word, which consists of adding three verbs with the letter of a word in the wazan اِنْفَعَلَ كلمة، واِفْتَعَلَ كلمة، وتَفَاعَلَ كلمة، وتَفَعَّلَ كلمة.والزيادات في الأفعال الثلاثية بثلاثة أحرف كلمة على وزن اِسْتَفْعَلَ.